Impact of different doses of cold water immersion (duration and temperature variations) on recovery from acute exercise-induced muscle damage: a network meta-analysis - Wang, Hai; Wang, Lu; Pan, Yingxu (Frontiers in Physiology, 2025)
ObjectiveThis network meta-analysis and systematic review evaluated the recovery impacts of varying cold water immersion (CWI) protocols on acute exercise-induced muscle damage.MethodsWe searched CNKI, PubMed, Cochrane Library, Web of Science, and Embase from January 2000 to September 2024 for randomized controlled trials examining CWI’s recovery effects on acute muscle damage. Data extraction, study screening, and risk of bias assessment were conducted independently by two reviewers. Analyses were performed using Stata 16.0.ResultsA total of 55 RCTs were included, with 42 reporting delayed onset muscle soreness (DOMS), 36 reporting jump performance (JUMP), and 30 reporting creatine kinase (CK) levels. Network meta-analysis showed that compared with the control group, MD-MT-CWI: Medium-duration medium-temperature cold water immersion (10–15 min, 11°C–15°C) [SMD = −1.45, 95%CI(-2.13, −0.77), P < 0.01] and MD-LT-CWI: Medium-duration low-temperature cold water immersion (10–15 min, 5°C–10°C) [SMD = −1.12, 95%CI(-1.78, −0.47), P = 0.01] significantly reduced DOMS; MD-LT-CWI (10–15 min, 5°C–10°C) [SMD = 0.48, 95%CI(0.20, 0.77), P = 0.01] and MD-MT-CWI (10–15 min, 11°C–15°C) [SMD = 0.42, 95%CI(0.15, 0.70), P = 0.02] significantly improved JUMP; MD-MT-CWI (10–15 min, 11°C–15°C) [SMD = −0.85, 95%CI(-1.36, −0.35), P = 0.01] and MD-LT-CWI (10–15 min, 5°C–10°C) [SMD = −0.90, 95%CI(-1.46, −0.34), P = 0.02] significantly reduced CK. Cumulative probability ranking showed that MD-LT-CWI (10–15 min, 5°C–10°C) was the most effective for improving JUMP and reducing CK, while MD-MT-CWI (10–15 min, 11°C–15°C) was the most effective for reducing DOMS.ConclusionDifferent dosages of cold water immersion (varying in duration and temperature) had different effects on recovery from acute exercise-induced muscle damage. We found that MD-LT-CWI (10–15 min, 5°C–10°C) was most effective for improving biochemical markers (CK) and neuromuscular recovery, while MD-MT-CWI (10–15 min, 11°C–15°C) was most effective for reducing muscle soreness. In practice, we recommend using MD-LT-CWI (10–15 min, 5°C–10°C) and MD-MT-CWI (10–15 min, 11°C–15°C) to reduce Exercise-induced muscle damage (EIMD). However, due to the limitations of the included studies, further high-quality studies are needed to verify these conclusions.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024602359.